Complicity [videorecording (DVD)] - Akasaka, Sayo; Chikaura, Kei; Fuji, Tatsuya, 1941-; Lü, Yulai, 1982- (Film Movement series., 2020)
Cheng Liang is a young Chinese illegal immigrant living in Japan. Desperate for work, he pretends to be someone else to get a job in a traditional Japanese soba restaurant. He starts his new life living and working with the elderly soba master (Tatsuya Fuji, In The Realm of the Senses), but always fearing to have his real identity disclosed at any moment.